MANAGEMENT OF THE ORGANIZATION OF PERSONNEL DOCUMENTS AND ACCOUNTING OPERATIONS RELATED TO PERSONNEL SETTLEMENTS - HURLOIU, Lăcrămioara; RUSU, Bianca; HURLOIU, Iulian (Annals of Spiru Haret University. Economic Series, 2024)
Lately in Romania it has been noted that there is a concernn for establishing ethical rules of the accounting profession to ensure professionalism, confidentiality and objectivity in performing the management work. The accounting theories underlying the management personel settlements assists the public entity tomeet its objectives through a systematic and methodical approach that evaluates and improves the effectiveness of the management system based on risk management, control and management processes.